2004
DOI: 10.1140/epjb/e2004-00218-6
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of the Wiedemann-Franz law in strongly-coupled electron-phonon system, application to the cuprates

Abstract: With the superconducting cuprates in mind, a set of unitary transformations was used to decouple electrons and phonons in the strong-coupling limit. While phonons remain almost unrenormalised, electrons are transformed into itinerent singlet and triplet bipolarons and thermally excited polarons. The triplet/singlet exchange energy and the binding energy of the bipolarons are thought to account for the spin and charge pseudogaps in the cuprates, respectively. We calculated the Hall Lorenz number of the system t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…As a general conclusion, the Wiedemann-Franz law can only account for a small part of the overall thermal conductivity in complex oxide systems. [82][83][84] Another contribution to the thermal conductivity could be related to a radiative heat transfer, which means that a certain amount of energy is transmitted by radiation through the material. 75 The comparison of the detector signals from the LFA measurements, which represent the time-dependent temperature prole at the sample rear surface, reveals rst a steplike signal increase followed by the typical time-dependent temperature evolution in LFA measurements (see Fig.…”
Section: Laser Ash Analysismentioning
confidence: 99%
“…As a general conclusion, the Wiedemann-Franz law can only account for a small part of the overall thermal conductivity in complex oxide systems. [82][83][84] Another contribution to the thermal conductivity could be related to a radiative heat transfer, which means that a certain amount of energy is transmitted by radiation through the material. 75 The comparison of the detector signals from the LFA measurements, which represent the time-dependent temperature prole at the sample rear surface, reveals rst a steplike signal increase followed by the typical time-dependent temperature evolution in LFA measurements (see Fig.…”
Section: Laser Ash Analysismentioning
confidence: 99%
“…Furthermore, as a large polaron system, lightly electron-doped SrTiO 3 possesses stronger electron-phonon coupling which may be another origin of the low Lorenz number. 45 However, further experimental and theoretical insight is required to gain a deeper understanding of WF law violation. In this study, even though there is an overestimation of κ ele , charge carriers (electrons) should play an important role in the different heat transfers of SLTO and STNO, since κ displays a consistent behavior with electron transport properties (summarized in Figure S3 of Supplementary).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, it has been reported that chemically doped or electrostatically controlled SrTiO 3 shows non‐Fermi liquid behavior despite of its T 2 ‐dependent resistance, 44 which may be a possible origin of the WF law violation. Furthermore, as a large polaron system, lightly electron‐doped SrTiO 3 possesses stronger electron‐phonon coupling which may be another origin of the low Lorenz number 45 . However, further experimental and theoretical insight is required to gain a deeper understanding of WF law violation.…”
Section: Resultsmentioning
confidence: 99%
“…confined dimensions 12,13 such as nano-wires, [14][15][16] quasi-1D systems, [17][18][19] and effective 0-D systems such as quantum dots, [20][21][22] , single molecule [23][24][25] and single atom 26 systems; under conditions of quantum criticality; [27][28][29][30][31] in superconductors; 16,[32][33][34][35][36][37][38] in superlattices and granular metals; [39][40][41][42][43] and in the presence of disorder.…”
mentioning
confidence: 99%
“…Therefore, there is no reason to expect that the Sommerfeld value holds for them, nor that the Lorenz number's value can only fall intermediately between the two limiting values. 3 In fact, deviations in the Lorenz number are nothing new and occur in various cases: confined dimensions 12,13 such as nano-wires, [14][15][16] quasi-1D systems, [17][18][19] and effective 0-D systems such as quantum dots, [20][21][22] , single molecule [23][24][25] and single atom 26 systems; under conditions of quantum criticality; [27][28][29][30][31] in superconductors; 16,[32][33][34][35][36][37][38] in superlattices and granular metals; [39][40][41][42][43] and in the presence of disorder. 44,45 However, here we consider a far more common, but yet to be explored, situation -the case of multi-band semiconductors, which are the most relevant case for next generation thermoelectric materials with complex bandstructures.…”
mentioning
confidence: 99%